THE EFFECT OF PRICE DISCOUNTS AND HALAL AWARENESS ON GRABFOOD PURCHASE DECISIONS WITH PURCHASE INTEREST AS AN INTERVENING VARIABLE - Yusuf, Doni; Ratno, Fernaldhi Anggadha (IQTISHADUNA, 2023)
This research aims to determine the Influence of Price Discount and Halal Awareness onPurchase Decision with Purchase Interest as the Intervening Variable among boarding houseresidents in the Salatiga area. This study adopts a quantitative research approach utilizingprimary data. Sample selection was carried out using Random Sampling, specifically employingrandom sampling where each respondent had an equal chance of being selected as a samplemember, resulting in a total of 97 respondents. The research findings indicate that the PriceDiscount variable significantly influences Purchase Decision positively. On the other hand, theHalal Awareness variable has a non-significant negative impact on Purchase Decision.Furthermore, Price Discount, Halal Awareness, and Purchase Interest significantly andpositively affect Purchase Decision. Purchase Interest significantly influences PurchaseDecision positively. Following path analysis testing, it was found that the Purchase Interestvariable effectively mediates between Price Discount and Halal Awareness concerning PurchaseDecision.